Nilai Ikhlas sebagai Pembentuk Pengendalian Emosi dalam Film Inside Out - Salwa Rismilillah Akmalia; Wildan Muttaqiin Sandah; Sara Samrotul Atkia; Fazar Sidik; Dadan Firdaus (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study analyzes the representation of emotions in the animated film Inside Out (2015) through the lens of Islamic Ethics and Mysticism (Akhlak Tasawuf), focusing on the value of sincerity (al-ridha) as a shaping force in the emotional regulation of the main character, Riley. Employing a descriptive qualitative method through documentation technique, the study examines scenes, dialogues, and character expressions reflecting processes of emotional acceptance and management. Data were analyzed using a combined framework drawing from the concept of rida in Sufi ethics and the Process Model of Emotion Regulation, particularly cognitive change and response modulation strategies. Findings indicate that al-ridha functions as an inner stabilizer guiding Riley toward nafs muthmainnah (a tranquil soul), evidenced in key scenes such as Riley's emotional disclosure to her parents and the transformation of her core memories. The concept of itsar (empathy) also emerges as a social dimension of emotional regulation that conventional psychological models tend to overlook. This study contributes an interdisciplinary framework bridging the psychological and spiritual dimensions of film analysis, while addressing a gap in research on animated films from an Islamic perspective.